Climate Change : Biological and Human Aspects - Cowie, Jonathan (Cambridge [England] ; New York : Cambridge University Press, 2013)
"This book is about biology and human ecology as they relate to climate change. Let's take it as read that climate change is one of the most urgent and fascinating science-related issues of our time and that you are interested in the subject: for if you were not you would not be reading this now. Indeed, there are many books on climate change but nearly all, other than the voluminous Intergovernmental Panel on Climate Change (IPCC) reports, tend to focus on a specialist aspect of climate, be it weather, palaeoclimatology, modelling and so forth. Even books relating to biological dimensions of climate change tend to be specialist, with a focus that may relate to agriculture, health or palaeoecology. These are, by and large, excellent value provided that they cover the specialist ground which readers seek. However, the biology of climate change is so broad that the average life-sciences student, or specialist seeking a broader context in which to view their own field, has difficulty in finding a wide-ranging review of the biology and human ecology of climate change. Non-bioscience specialists with an interest in climate change (geologists, geographers, atmospheric chemists, etc.) face a similar problem"--
Includes bibliographical references and index.
Keywords: Climatic changes -- History; Bioclimatology; Paleoclimatology; Climatic changes; Human beings -- Effect of environment on; Human ecology